Mechanical properties of glass fibre reinforced polypropylene thermoplastic pipes - Kareem, Yusuf Abiola (My University, 2008)
ABSTRACT Glass fiber reinforced polypropylene pipes were fabricated from 6-10 layers of “Plytron” GN638T 25mm wide glass fiber pre-impregnated polypropylene tapes using filament winding/tape laying process, in-situ consolidation on a 1000mm long mandrel. Infrared heater and heat gun were used in heating the incoming tapes and the substrate at the nip point. The effects of process pressure and temperature on the mechanical properties were investigated by testing samples of test laminates and fabricated pipes for their mechanical properties. Results indicated that the mechanical properties of the test samples and pipes were affected by changes in process temperature and pressure, with an optimum process pressure and temperature being 16.8KPa and 2800C respectively. The cost analysis of the fabricated pipes indicated that the materials and method of production employed in this research could be utilized to an economic advantage when compared with the prices of the same type of pipes in SA market.
Keywords: glass fibre polypropylene; thermoplastic pipes